Research on new type MRE isolator and its mechanical model. (May 2014) - Tu, J. W.; Tu, B.; Mei, S. T.; Huang, L.; Xu, J. Y.
Abstract : A new type of seismic isolator with adjustable stiffness is proposed, based on the smart material of magnetorheological elastomers (MREs). This paper specifies the working principle of the isolator, analyses magnetic induction distribution of three different types of MRE isolators, which are unicoil magnetic energy input, twin coil magnetic energy input, and laminated steel plate coiling magnetic energy input respectively. The research shows that the third type of input produces relatively greater magnetic induction in the elastomer area, compared with the first two, and the magnetic field is evenly distributed in MRE area, therefore, it is the best structure. Eventually, the mechanical model of MRE isolator made of two steel slices and one elastomer slice is established together with the mechanical model made of multi-steel slices and multi-elastomer laminated structure. Furthermore, the numerical analysis is completed and the results show that MRE isolators have content adjustable behaviour.